Transformation of Learning Al-Qur'an Hadith with Big Book Media at Madrasah Ibtidaiyah Thoriqun Najah - Endang, Ujang; Daryaman (Journal of Asian Primary Education (JoAPE), 2024)
In the context of learning activities at Madrasah Ibtidaiyah Thoriqun Najah, several problems have been faced, such as low student learning outcomes, shortcomings in teacher administration, and limited learning media. This research aims to explore how to improve the quality of learning in the era of globalization. The method used is Classroom Action Research (PTK) with data collection techniques through observation, tests, and qualitative data analysis. The results showed an improvement in the preparation of the Learning Implementation Plan (RPP), teacher performance, and student learning outcomes with the use of "Big Book Learning Media". The conclusion of this study is the importance of improving teacher competence, better administration, and effective use of learning media. Teachers need to understand curriculum standards, utilize technology, and involve parents in the learning process. Collaboration between related parties is key in improving learning effectiveness and student achievement in the era of globalization.